Impact of different classes of antidepressants on sleep and wakefulness regulation in depression - G. M. Usov; D. Yu. Kolomytsev; L. M. Lomiashvili (Неврология, нейропсихиатрия, психосоматика, 2022)
Sleep disturbances are common in patients with mental disorders. Sleep disturbances, in particular insomnia, are widespread in depression. Depressed patients have a lot of sleep complaints that are often confirmed by polysomnography. Most antidepressants impair sleep, so drugs that help to restore sleep are of particular value in clinical practice. Agomelatine (valdoxan) rapidly improves sleep in depressed patients by making it easier to fall asleep, increasing total sleep time, duration of rapid eye movement (REM), and slow-wave sleep (SWS), and improving functioning during the day.